TEACHING ENGLISH TO YOUNG STUDENTS - Kabilova Kamola; Tulkinova Dilshoda G‘ofurjon qizi (Ustozlar uchun, 2025)
Annotation: This article discusses effective methods, didactic approaches and psychological and pedagogical features of teaching English to young students. The importance of organizing English lessons in an interesting and effective way, using visual, audiovisual and interactive tools appropriate to their age when working with children in preschool and primary education is substantiated. Also, ways of forming motivation in learning a foreign language, developing oral speech and forming a positive attitude towards the language are analyzed.